Why Vouchers Aren’t Good for the (Re)Public - Itkonen, Tiina (Allies for Education, 2017)
Vouchers have not been an option in California because our state’s constitution prevents using public money for religious or private school. But this may change soon, as the Supreme Court is about to hear case about this. Depending on how the Court decides, school boards could then pass programs that use taxpayer funds for private schools.